Biodegradable electrospun PLA-PHB fibers plasticized with oligomeric lactic acid. (September 2020) - Arrieta, Marina P.; Perdiguero, Miguel; Fiori, Stefano; Kenny, José María; Peponi, Laura
Abstract: In this paper flexible electrospun mats based on poly(lactic acid) (PLA) blended with 25 wt% of poly(hydroxibutyrate) (PHB) and further plasticized with three different concentration of oligomeric lactic acid (OLA) were developed. The morphological, structural, thermal and mechanical performance of electrospun mats was evaluated. OLA improves the crystallization rate of PLA presenting better interaction with PLA than with PHB. The incorporation of OLA to PLA-PHB blends produced a decrease on the viscosity of the polymeric solutions, leading to a reduction of the fibers diameters by increasing the amount of OLA plasticizer in the final blends. The highest amount of OLA of 20 wt% respect to PLA-PHB blend produced some bead defects in the fibers, which leads to a reduction of the mechanical performance of woven no-woven electrospun mats. Furthermore, all the electrospun mats were disintegrated in composting conditions showing their interest as compostable materials. The ternary system PLA-PHB-OLA15, showed the best results in term of structural and mechanical properties as well as appropriate disintegration in compost suggesting their potential applications as agricultural mulch films. Highlights: Woven no-woven plasticized electrospun fibers have been successfully obtained. Blends of PLA-PHB with different plasticizer composition have been obtained by electrospinning techniques. The mechanical response can be tuned with the different amount of plasticizer. Biodegradable electrospun mats for potential application in agriculture have been studied.